A change in the taxonomic rank of Senna andhrica P. V. Ramana, J. Swamy & M. Ahmed. (Fabaceae: Caesalpinioideae) - Jiang, Kai-Wen (Phytotaxa, 2021)
Senna andhrica P. V. Ramana, J. Swamy & M. Ahmed. is better treated as a variety of S. occidentalis (L.) Link, as S. occidentalis var. andhrica (P. V. Ramana, J. Swamy & M. Ahmedullah) K. W. Jiang, based on its diagnostic morphological characters of unifoliolate leaves and 2–3 carpellate gynoecium. Attention is drawn to an error in the original figure published with the description of Senna andhirica, the seeds specified by the authors are actually belong to a taxon of Crotalaria.